Water stable isotopes in the Yarlungzangbo headwater region and its vicinity of the southwestern Tibetan Plateau. Issue 1 (1st December 2016) - Ren, Wei; Yao, Tandong; Xie, Shiyou
Abstract : Various types of water samples across the Yarlungzangbo headwater region and its vicinity of the southwestern Tibetan Plateau were collected in summer 2012 for isotopic analysis to augment our specific understanding of regional hydroclimate. In the upper Yarlungzangbo system, contribution of more isotopically depleted tributary influx rather than evaporation is identified as the major hydrological process, and this causes generally progressive depletion in main flow isotopes downstream/eastward. On the regional scale (from the middle Yarlungzangbo basin to the western vicinity of the Yarlungzangbo headwaters), one of the clearest findings is the synchronous increases in river/stream δ 18 O and d-excess (d-excess= δD – 8δ 18 O) from east to west. From a geographical and climatological perspective, these can be explained by increasing contributions of summer-time continental/local recycled vs. monsoonal moisture or winter-spring vs. summer monsoon precipitation in the surface runoff generation westward. The Yarlungzangbo headwaters are at a critical transition between the Indian monsoon system in the east and the westerly one in the west as revealed by the intermediate d-excess and δ 18 O values, while the Himalaya region farther west (i.e. Pulan region) is predominated by the continental recycled moisture as revealed by the highest d-excess and δ 18 O values. Furthermore, based upon existing isotopic and meteorological data, a predicted local evaporation line for the Yarlungzangbo headwater region and its vicinity is proposed, which can further help to assess how local hydroclimate affect water stable isotopes. Results of this study provide a baseline for isotopic hydroclimate research in the southwestern Tibetan Plateau.